2018
DOI: 10.1038/s41598-018-23970-7
|View full text |Cite
|
Sign up to set email alerts
|

Low heart deceleration capacity imply higher atrial fibrillation-free rate after ablation

Abstract: How deceleration capacity (DC) and acceleration capacity (AC) of heart rate associated with atrial fibrillation (AF) and ablation is still not clear. The dynamic changes of AC, DC and conventional heart rate variability (HRV) parameters were characterized in 154 subjects before circumferential pulmonary veins isolation (CPVI) and three days, 3 months and 6 months after CPVI. The DCs of the recurrent group decreased significantly at each time point after CPVI; the DCs of the recurrence-free group before CPVI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Theoretically, DC index could reflect the cardiac vagal modulation on heart rate [7, 10, 13, 31, 32]. When applied PRSA to heartbeat intervals for assessing vagal tone modulation, the anchor points selected according to Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, DC index could reflect the cardiac vagal modulation on heart rate [7, 10, 13, 31, 32]. When applied PRSA to heartbeat intervals for assessing vagal tone modulation, the anchor points selected according to Eq.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to heartbeat time series, the deceleration capacity (DC) of heart rate quantified by PRSA also reflects parasympathetic/vagal control of heart rate [7]. Despite the growing application of DC [813], the method is affected by one shortcoming: non-vagally mediated abnormal variants of sinus rhythms in heartbeat interval time series are used to quantify DC, thus confounding the evaluation of cardiac vagal modulation. Previous studies reported that the presence of erratic sinus rhythm, sinus alternans, and their variants, influence values of HRV indices including root-mean-square of successive differences of normal-to-normal interbeat intervals (rMSSD), the percentage of normal-to-normal intervals > 50 ms different from the previous interval (pNN50), and the amount of variance in normal-to-normal intervals at respiratory frequencies (HF, 0.15–0.4 Hz) [1416].…”
Section: Introductionmentioning
confidence: 99%
“…ANS tone was assessed using (1) = 2 using up to 100,000 RR intervals from ambulatory monitoring, as described elsewhere. 3 For AC/DC measurement consecutive RR intervals varying more than 20% in length were automatically excluded from analysis to minimize artifacts interference, a cut-off value used by previous studies. 3 HRT parameters include TO and TS that were calculated from RR tachograms before and after a premature ventricular contraction (PVC).…”
Section: Autonomic Nervous System Tone Assessmentmentioning
confidence: 99%
“…3 For AC/DC measurement consecutive RR intervals varying more than 20% in length were automatically excluded from analysis to minimize artifacts interference, a cut-off value used by previous studies. 3 HRT parameters include TO and TS that were calculated from RR tachograms before and after a premature ventricular contraction (PVC). TO assesses early sinus rate acceleration and TS assesses late deceleration following PVC and the method of determination is described elsewhere.…”
Section: Autonomic Nervous System Tone Assessmentmentioning
confidence: 99%
See 1 more Smart Citation